The relationship of 3′UTR HLA‐G14‐bp insertion/deletion and +3142 C/G polymorphisms and soluble HLA‐G expression with gynecological cancers: An updated meta‐analysis. Issue 7 (6th June 2022) - Tizaoui, Kalthoum; Jalouli, Maroua; Boujelbene, Nadia; Harrath, Abdel Halim; Ouzari, Hadda‐Imene; Rizzo, Roberta; Zidi, Inès
Abstract: Objectives: Human leukocyte antigen‐G (HLA‐G) is implicated in several cancers and is considered to be an immune checkpoint regulator. We determined the association between polymorphisms in the 3′ untranslated region of HLA‐G and soluble HLA‐G (sHLA‐G) expression with gynecological cancers (GCs). Methods: A meta‐analysis was conducted to examine the association between HLA‐G14‐bp insertion ( I )/ deletion ( D ) and +3142C/G polymorphism in GC and to evaluate sHLA‐G expression Results: We revealed a significant association between the +3142C/G polymorphism and invasive cervical cancer (ICC) based on the allelic model G versus C (odds ratio [OR] = 0.738, 95% confidence interval [CI] = 0.563–0.966, p  = 0.027), dominant GG+GC versus CC (OR = 0.584, 95% CI = 0.395–0.862, p  = 0.007), and codominant GG versus CC (OR = 0.527, 95% CI = 0.312–0.891, p  = 0.017) models, suggesting that the G allele and GG genotype are protective against ICC. In gynecological precancerous patients with human papillomavirus (HPV) infection, we found that the 14‐bp I/D under the codominant DD versus DI model (OR = 0.492, 95% CI = 0.241–1.004, p  = 0.051) was of borderline significance. Soluble HLA‐G levels were significantly higher in patients compared with healthy controls (standardized mean differences [SMD] = 1.434, 95% CI = 0.442–2.526, p  = 0.005). Stratification by cancer type revealed that the sHLA‐G levels were significantly increased in cervical cancer (SMD = 4.889, 95% CI = 0.468–9.310, p  = 0.030) and in subjects of Asian ethnicity (SMD = 4.889, 95% CI = 0.467–9.309, p  = 0.030). Conclusions: HLA‐G14‐bp I/D and +3142 C/G polymorphisms are associated with GC and HPV‐associated cervical cancer. In addition, we found significantly increased sHLA‐G levels in cancer patients. These results provide a basis for further studies in diagnostics and immunotherapy of GC. Abstract : Human leukocyte antigen‐G  ( HLA‐G ) 14‐bp insertion ( I )/ deletion ( D ) and +3142 C/G polymorphisms are associated with gynecological cancer (GC) and human papillomavirus‐associated cervical cancer. Soluble HLA‐G is significantly increased in GC.